2020
DOI: 10.2147/copd.s274728
|View full text |Cite
|
Sign up to set email alerts
|

<p>COPD and Osteoporosis: Associated Factors in Patients Treated with Inhaled Corticosteroids</p>

Abstract: Purpose: Osteoporosis is a systemic skeletal disease with a consequent increase in fractures rates. Osteoporosis may be primary which is related with normal aging, or secondary which occurs in the presence of an underlying disease or medication. Osteoporosis is one of the significant comorbidities in chronic obstructive pulmonary disease (COPD). In this study, we aimed to investigate the presence of osteoporosis and the influencing factors in COPD patients. Patients and Methods: This is a two-group comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…A variety of inflammatory factors are involved in the activation of RANKL ( Figure 1 ). Additionally, prolonged breathing disturbances led to metabolic disorders that left patients in a state of malnutrition and affected the normal remodeling function of bone tissue ( Ozcakir et al, 2020 ). Corticosteroid application in clinical treatment was also a non-negligible factor that threatens bone health.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of inflammatory factors are involved in the activation of RANKL ( Figure 1 ). Additionally, prolonged breathing disturbances led to metabolic disorders that left patients in a state of malnutrition and affected the normal remodeling function of bone tissue ( Ozcakir et al, 2020 ). Corticosteroid application in clinical treatment was also a non-negligible factor that threatens bone health.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that a large number of people with COPD sometimes experience respiratory symptoms, despite the chronic use of several medications [34]. Moreover, it was documented that the inhaled corticosteroids are the secondary cause of osteoporosis in elderly patients with COPD [15], which can have a negative impact on their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Drug treatments in these patients have the main aims of controlling symptoms, reducing the frequency of disease exacerbation, and improving patients' performance and quality of life [13,14]. However, it can be associated with serious complications such as osteoporosis [15]. erefore, the need for proper planning for the proper management of these patients is strongly felt.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis a systemic skeletal disease is one of the significant comorbidities in chronic obstructive pulmonary disease (COPD). With an aim to aim to investigate the presence of osteoporosis and the factors that influence the prevalence of osteosporosis authors conducted study at the outpatient clinics at the Departments of Physical Medicine and Rehabilitation and Pulmonary Diseases in Bursa Uludag University Hospital, a tertiary reference center, in the northwest region of Turkey in 63 COPD patients ( Ozcakir et al, 2020 ) [M]. Thirty COPD patients were on inhaled corticosteroid (ICS) and the control group had 33 patients.…”
Section: Systemic Glucocorticoids [Sed-15 906; Seda-33 841; Seda-34 653; Seda-35 719; Seda-36 604; Seda-37 492; Seda-38 425 Seda-42]mentioning
confidence: 99%